Investment Grants and Firms' Productivity: How Effective Is a Grant Booster Shot? - Fernando Alexandre; Miguel Chaves; Miguel Portela (Institute of Labor Economics (IZA), 2022)
This paper investigates the effect of awarding a second investment grant to the same firm. We implement a Regression Discontinuity Design strategy using a very rich firm-level administrative database, which allows us to link applications to grants and their scores to firms' performance. Overall, our results show a positive and significant impact of an investment grant booster shot on firms' labour productivity. This effect is significantly larger than the effect of a single grant. A more granular analysis shows a strong impact of awarding a second grant to small-sized firms. However, we found no effect on micro, medium and large-sized firms. Our results suggest that the characteristics of the targeted firms, namely firm size, matter for the effectiveness of awarding a second grant to the same firm.
Keywords: D22; H25; L25; L52; 330; industrial policy; investment grants; multiple treatments; productivity